Change in Patient Flow in the Epilepsy Care Network Due to Novel Coronavirus Infection: An Opportunity to Strengthen Local Interdisciplinary Epilepsy Care With General Physicians - Fujimoto, Ayataka; Sato, Keishiro; Enoki, Hideo (Frontiers in Neurology, 2020)
Introduction: Novel coronavirus disease 2019 (COVID-19) continues to infect populations worldwide. We hypothesized that patient flow in epilepsy care would change as a result of the COVID-19 pandemic. The purpose of this study was to compare the number of patients who visited our epilepsy center before and during the first peak of the pandemic. Methods: We recorded the number of patients with epilepsy referred from general physicians (GPs) to our hospital (GP–H group), the number of patients who visited our hospital on a regular basis (R group), and the number of patients referred from our hospital to GPs (H–GP group) between July 2019 and June 2020. Results: A total of 1839 epilepsy patients made 4197 visits to our hospital, 979 males and 860 females (age range, 0–94 years; mean age, 37.6 years; median age, 34 years). There were 433 patients in the GP–H group (247 before the pandemic, 186 during the first peak of the pandemic; p = 0.007). In the R group, 1406 patients made 3764 visits (1992 visits before the pandemic, 1772 during the first peak of the pandemic). In the H–GP group, 135 patients were referred to GPs (47 patients before the pandemic, 88 patients during the first peak of the pandemic; p = 0.023). Conclusion: Changes to patient flow in the epilepsy care network due to COVID-19 presented an opportunity to reorganize local interdisciplinary epilepsy care.